2021
DOI: 10.3389/fonc.2021.708765
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor miRNA in Cancer Cells and the Tumor Microenvironment: Mechanism of Deregulation and Clinical Implications

Abstract: MicroRNAs (miRNAs) are noncoding RNAs that have been identified as important posttranscriptional regulators of gene expression. miRNAs production is controlled at multiple levels, including transcriptional and posttranscriptional regulation. Extensive profiling studies have shown that the regulation of mature miRNAs expression plays a causal role in cancer development and progression. miRNAs have been identified to act as tumor suppressors (TS) or as oncogenes based on their modulating effect on the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 158 publications
(201 reference statements)
1
76
0
Order By: Relevance
“…The main genetic alterations affecting carcinogenesis involve changes in tumor suppressors (APC, p53 BRCA2, PTCH, NF1, VHL, Rb BCL2, SWI/SNF, p16, CD95, ST5, YPEL3, ST7, and ST14) and oncogenes (Ras, jun, fas, erbA, abl, raf, gsp, sis, erbB, and fms) in addition the onset and progression of oral cancer involve changes of DNA methylation, histone modifications, and non-coding alterations of RNA, including microRNAs (miRNA) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main genetic alterations affecting carcinogenesis involve changes in tumor suppressors (APC, p53 BRCA2, PTCH, NF1, VHL, Rb BCL2, SWI/SNF, p16, CD95, ST5, YPEL3, ST7, and ST14) and oncogenes (Ras, jun, fas, erbA, abl, raf, gsp, sis, erbB, and fms) in addition the onset and progression of oral cancer involve changes of DNA methylation, histone modifications, and non-coding alterations of RNA, including microRNAs (miRNA) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are ncRNAs with a length of 20–25 nucleotides that influence gene expression after transcription. 29 The majority of mature miRNA sequences are found in ncRNA introns, ncRNA exons, and pre-mRNA introns, and miRNAs are processed from protein-coding gene introns or RNA polymerase II-specific transcripts of separate genes. 30 , 31 Increasing evidence demonstrates that miRNAs act as key regulators of development and cellular homeostasis by controlling a variety of biological processes.…”
Section: Overview Of Mirnasmentioning
confidence: 99%
“…One mRNA might be targeted by numerous related or unrelated miRNAs [ 33 , 34 ]. It has been reported that one miRNA complex can target almost two hundred genes of variable functions [ 35 ]. About 60% of human genes can be targeted by these miRNAs, once their corresponding mRNAs targets are regulated by miRNA, influencing various pathways, including cancer [ 36 , 37 ].…”
Section: Mirnas—biogenesis Biochemistry and Functionsmentioning
confidence: 99%